Tennis masters. Nitto vs next generation ATP finals - Sánchez-Pay, A.; Navarro-Cuenca, J. J.; Sánchez-Alcaraz, B. J. (Coaching and Sport Science Review, 2020)
The objective of this study was to know the influence of the modification of the tournament regulations between the 2019 Nitto ATP Finals and Next Gen tournaments in relation to physical and technical parameters. In order to do this, 100% of the sets played (34 of the Nitto ATP Finals and 55 of the Next Gen) of a total of 30 matches were analysed. The data was selected from the information published on the Official Website of the Tennis ATP (https://atp.com/). The results of this study show that the specific tournament regulations in the Next Gen ATP Finals (matches to the best of 5 sets of four games, elimination of the advantages and use of the "golden point", and the no-let rule) could influence the duration of the match and the number of total break opportunities, although not significantly. The percentage of first serves was similar between both tournaments, so despite including the no-let rule, the time interruptions between the first and second serves were equivalent.